2006
DOI: 10.1104/pp.105.071845
|View full text |Cite
|
Sign up to set email alerts
|

Function and Characterization of Starch Synthase I Using Mutants in Rice

Abstract: (A.M., H.H.) Four starch synthase I (SSI)-deficient rice (Oryza sativa) mutant lines were generated using retrotransposon Tos17 insertion. The mutants exhibited different levels of SSI activities and produced significantly lower amounts of SSI protein ranging from 0% to 20% of the wild type. The mutant endosperm amylopectin showed a decrease in chains with degree of polymerization (DP) 8 to 12 and an increase in chains with DP 6 to 7 and DP 16 to 19. The degree of change in amylopectin chain-length distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
343
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(375 citation statements)
references
References 67 publications
20
343
2
Order By: Relevance
“…The different amounts of SBEI, SBEIIa, and SBEIIb distributed in the four heterogeneous starch granules caused different binding amounts of SSI. It has been reported that SSI plays a critical role in generating chains of DP 8-12 from chains of DP 6-7 that emerge from the branch points of amylopectin, carried out by SBE (Fujita et al, 2006). This finding greatly helped to elucidate the gradually decreasing ratio of DP 6-12 in the four TRS heterogeneous starch granules (Fig.…”
Section: Granule-bound Amylopectin Biosynthetic Enzymes Are An Importmentioning
confidence: 78%
See 1 more Smart Citation
“…The different amounts of SBEI, SBEIIa, and SBEIIb distributed in the four heterogeneous starch granules caused different binding amounts of SSI. It has been reported that SSI plays a critical role in generating chains of DP 8-12 from chains of DP 6-7 that emerge from the branch points of amylopectin, carried out by SBE (Fujita et al, 2006). This finding greatly helped to elucidate the gradually decreasing ratio of DP 6-12 in the four TRS heterogeneous starch granules (Fig.…”
Section: Granule-bound Amylopectin Biosynthetic Enzymes Are An Importmentioning
confidence: 78%
“…However, when diverse ranges of genes are mutated, distinct effects on granule morphology in a seed are detected. For example, once the soluble starch synthase OsSSIIIa/Flo5, which is responsible for the extension of relatively long chains of both amylopectin B2 and B3 to B4 (Gao et al, 1998;Jane et al, 1999;Fujita et al, 2006), is eliminated from the genome, a phenotype of loosely packed central portions exhibiting a floury white-core endosperm is detected. The granules located in this region are smaller than those of the parental control and exhibit round morphology with no sharp edges, while the peripheral region in ssIIIa/flo5 contains normal compound starch (Ryoo et al, 2007).…”
mentioning
confidence: 99%
“…Thus, SSIII appears to affect the entire range of chains that constitute crystalline lamellae as well as those that extend through multiple crystalline clusters. In contrast, SSI and SSII are required for the normal abundance of discrete, continuous spans of chain length, which can be explained by substrate preference Zhang et al, 2004Zhang et al, , 2008Delvallé et al, 2005;Nakamura et al, 2005;Fujita et al, 2006).…”
Section: Effects Of Ssiii Deficiency In Single Mutantsmentioning
confidence: 99%
“…Previous studies have focused on genes directly involved in the biosynthesis/metabolism of starch, protein and fat [66][67][68][69][70][71][72][73]; our analysis suggests that many other genes may also be involved in seed quality control. Analysis of the underlying complex regulatory network should broaden our understanding of the relevant regulatory mechanisms.…”
Section: Genes Associated With Seed Quality Control Are Involved In Dmentioning
confidence: 82%